1992
DOI: 10.1038/ki.1992.181
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model of lead nephropathy. I. Continuous high-dose lead administration

Abstract: This study followed the progression of lead nephropathy in male Sprague-Dawley rats (E) administered lead acetate (0.5%) continuously in drinking water for periods ranging from 1 to 12 months. Control animals (C) were pair-fed. Observations included renal pathology by light and electron microscopy, wet and dry kidney weights, and glomerular filtration rate (GFR) to assess renal function. Urinary excretion of lead, the enzymes N-acetyl-beta-D-glucosaminidase (NAG) and glutathione-S-transferase (GST), and brush … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 32 publications
2
50
1
1
Order By: Relevance
“…furthermore, lead can induce pathological changes in the structure and function of this organ (Khalil-Manesh et al 1992). The results of research on the lead influence on the soD activity are divergent.…”
Section: Resultsmentioning
confidence: 99%
“…furthermore, lead can induce pathological changes in the structure and function of this organ (Khalil-Manesh et al 1992). The results of research on the lead influence on the soD activity are divergent.…”
Section: Resultsmentioning
confidence: 99%
“…A common finding in experimental studies on rats is that Pb seems to cause an increase in kidney weight [43][44][45][46][47]; however, there are also some studies reporting no effect on kidney …”
Section: Associations With Organ Weightsmentioning
confidence: 99%
“…[16] High levels of lead accumulate in tissues where lead-induced pathological changes occur in their structure and function. [17] Specifically, lead is known to cause impairment of liver functions and kidney dysfunction as well. [18] The present study supports that lead acetate treated chick embryo liver showed significant toxic changes which are manifested as hepatic damage ( Figure: 2&3).…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%